Drawing and reinventing landscape - Balmori, Diana (Chichester, West Sussex : John Wiley & Sons Inc, 2014)
In landscape architecture, representation is a hot topic in landscape architecture. While computerization has been a catalyst for change across many fields in design, no other design field has experienced such drastic reinvention as has landscape architecture. As the world urbanizes rapidly and our relationship with nature changes, it is vitally important that landscape designers adopt innovative forms of representation - whether digital, analog, or hybrid. In this book, author Diana Balmori explores notions of representation in the discipline at large and across time. She takes readers from landscape design's roots in seventeenth-century France and eighteenth-century England through to modern attempts at representation made by contemporary landscape artists. Addresses a central topic in the discipline of landscape architecture -- Features historic works and those by leading contemporary practitioners, such as Bernard Lassus, Richard Haag, Stig L Andersson, Lawrence Halprin, and Patricia Johanson. Written by a renowned practitioner and educator. Features 150 full-color images. Drawing and Reinventing Landscape, AD Primer is an informative investigation of beauty in landscape design, offering inspiring creative perspectives for students and professionals.
Epigraph -- Acknowledgements -- Foreword / Michel Conan -- Introduction -- The contemporary reinvention of landscape architecture and its representation -- The pleasure of drawing -- Notebooks, early sketches and late drawings -- Contemporary landscape architects and landscape artists -- Historical issues in landscape architecture representation -- Contemporary issues deriving from change.
Landscape Architects: Landscape Urbanism, Bernard Lassus, Patricia Johanson, Richard Haag (Rich Haag Associates), Stig L. Andersson (SLA), Lawrence Halprin (Lawrence Halprin and Associates), Diana Balmori (Balmori Associates).
Includes bibliographical references (pages 192-193) and index.
Text in English.
Description based on print version record.
Keywords: Landscape architectural drawing; ARCHITECTURE / Landscape; GARDENING / Garden Design; GARDENING / Landscape; Landscape architectural drawing; Electronic books; Electronic books